SKRINING PLASMA NUTFAH PADI TERHADAP CEKAMAN KEKERINGAN - Rina Hapsari Wening; Untung Susanto (Widyariset, 2014)
Rice germplasm is a source of genetic traits in the development of high yielding varieties of rice. This study aims to obtain drought tolerant trait of rice germplasm so that it could be used as a donor in the development of drought tolerant rice. The experiment was conducted from April to September 2010 in the Experimental Site of Indonesian Agriculture Environment Research Institute, Jakenan, Pati, Jawa Tengah using Randomized Block Design (RBD) with three replications. The material used is 64 accessions of rice germplasm and 6 varieties of checks. The result showed that the character of maturity age and the number of filled grain per panicle have posi- tive correlation with grain yield per plant. Four accessions namely, Pelempung Jambi, Padi Jarum Emas, Padi Kuning, Cempo Abang Ner and Botel, have been selected tolerant to drought stress and high yielding based on the character of grain yield per plant, maturity age, and the number of filled grain per panicle. Based on rolling and drying leaf on heading phase, the fifth accessions have tolerance to drought stress with score 1–5. Fifth accession can be used as donor on development of drought tolerant rice.